Être insulaire et créole au temps des colonies - Éric Fougère (Carnets)
Culturally valued, politically controversial, the notion of identity, philosophically, turns out to be an uncertain concept: undifferentiated similarity, but differentiated feeling of belonging to values which define us as both identical, and different. If the island has something to do with identity it is because it is a minority figure whose history has often brought it into contact with colonialism: it seems that claims of identity are often related to dominated minorities. Rather than an identity of withdrawal, it is towards an identity of Relation that Glissant takes us by resorting to the notion of Archipelago and by betting on Diversity. Before him, it was a New Caledonian writer, Jean Mariotti, who preferably stages an insularity of the in-between based on the games of a multiple identity in the making impossible to realize, which returns to otherness which constitutes it, while overthrowing it. We are then in the presence of contradictory and fragmented identities that their gap opens up to their inner distance and that their juxtaposition makes similar to what each is in the other.